PELAKSANAAN TOILET TRAINING DALAM PRESPEKTIF ISLAM DI RA AL FURQON 2 KEDUNGWARU TULUNGAGUNG - Rohmah, Liatul; Zuhriyah, Lailatuzz (Universitas Islam Negeri Ar-Raniry, 2020)
Toilet training is a way to train children in controlling their bodies when going to defecate (BAB) and urinate (BAK), carried out when the childrenare ready both physically, mentally and intellectually. In kindergarten aged, they should be able to control the urinary tract so that children no longer wet or bulge. The purpose of this study was to determine the implementation of toilet training in the perspective of Islam in RA Al Furqon 2 Kedungwaru Tulungagung. The method used is descriptive qualitative method, where researchers as key instruments. The results of this study: 1) the teacher explains cleanliness, purity and impurity, and manners when defecating, urinating and how to use the toilet and clean it. 2) Taught prayer reading into the toilet and exiting the toilet, 3) gives students the opportunity to defecate (BAB) or small (BAK). ) When they find a sign of students want to urinate (BAK) and defecate (BAB) and escort him to the toilet. 5) students are taught to queue, alternately, and orderly in using the toilet, 6) teach to flush the toilet and get students to wash their hands properly after defecating (BAB) and urinating (BAK) 7) getting students used to take off and use own clothing after large and small waste 8) give praise and appreciation. Toilet Training at RA Al Furqon 2 has been successful because there were no students who wet their bed.